Dr. Ali Al Qasimi's efforts in the historical dictionary methodology: Through his membership in the two scientific committees for the two historical dictionary projects of the Arabic language in (Doha) and (Sharjah) - Singal, Rajaa; Jabbar, Morouge (Al-Adab Journal, 2024)
There is no doubt that the draft historical dictionary of our Arabic language; It is the project of the nation, which the Arab linguistic academies set out to accomplish despite the many challenges and obstacles that accompanied its path. Arab experts set out to embody the idea of the project and show it to the public. They were, and still are, making every effort to complete the process of compiling the (Historical Dictionary of the Arabic Language), and among the most important linguists, linguists, and lexicographers who had the lead in building this project; He is the distinguished Iraqi scholar, Dr. Ali Al-Qasimi, who had a prominent role in crystallizing the basic plan for the historical dictionary, and in developing a new vision based on Western visions. Because of the qualifications he acquired from his coexistence with the latest linguistic theories; He was, and still is, highly motivated to spread his vision in conferences and meetings related to the project, especially if we know that he is an active member of the scientific committees for the two projects of the Historical Dictionary of the Arabic Language in (Doha) and (Sharjah). Perhaps his book (The Historical Dictionary of the Arabic Language Industry); The best evidence of this, as it is a summary (of the scientific plan) for the project of the historical dictionary of the Arabic language, which was assigned to it by the Scientific Council of the Union of Arab Linguistic Academies. In this research, we will present the most important steps and methodologies for classifying the historical dictionary of the Arabic language, as defined by Dr. Al-Qasimi.